Study of the Quantum Dot and Theoretical Model of Hamiltonian of An Electron Interaction with Longitudinal Optical Phonons - Ramshankar Chaudhary (International Journal of Scientific Research in Science and Technology, 2025)
In this present paper, we presented about the study of the quantum dot and present a theoretical model of Hamiltonian of an electron interaction with longitudinal optical phonons.
Keywords: Electron; Phonon Interaction; FTL; Momentum; Quantum Dot